Grain yield, competitive indices and water use under soybean (Glycin max) - based intercropping systems in south-eastern Rajasthan - PRASAD, S N; SINGH, RATAN; SINGHAL, A K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy season          of 1990-91 to 1992-93 at Kota to study the effect ofintercropping soybean [Glycin max (L.) Merr.] with sorghum [Sorghum bicolor (L.) Moench.] and pigeonpea [Cajanuscajan(L.) Millsp.) in 2: 1, 4: 1 and 6: 1 rows 30 cm apart     on productivity, water use and competitive indices. Intercropping systems were found more productive than sale soybean. Intercropping soybean with pigeonpea in 4 : 1 row irrangement proved superior to other treatments and yielded 712 kg/ha soybean and 830 kg/ha pigeonpea seed, which amounted to 1 493 kg/ha soybean-equivalent yield  compared with 1 086 kg/ha sole-soybean yield. This system also recorded the highest land-equivalent ratio 0.26). Intercropping systems showed higher water use and water-use eniciency then sole soybean. The values of competitive ratio (CR), relative crowding coefficient (RCC) and aggressivity indicated that sorghum and pigeonpea were dominant over soybean. The aggressivity values of soybean were negative in all the intercropping systems, whereas CR and RCC values remained